PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE BERCERITA SISWA KELAS V SEKOLAH DASAR - Sri Rezki Maulina Azmi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2019)
This Classroom Action Research (CAR) aims to improving the speaking ability of fifth grade students of SD Negeri 010145 Labuhan Ruku in the 2018/2019 school year in particular. This classroom action research was carried out in two cycles, in the fifth grade students of Public Elementary School 010145 Labuhan Ruku 2018/2019 academic year, which amounted to 16 people as the research subjects. Data collection methods used in this study are: 1) tests, 2) observations, and 3) documentation. Descriptive statistical data analysis techniques are used to analyze quantitative data, namely mean values, while the qualitative data analysis is used as a groove model. The results of the study indicate that the use of storytelling methods can enhance learning activities and speaking skills.